Measuring Learning Presence as Fourth Dimension in the Community of Inquiry Survey: Defining Self-Regulation Items and Subscales through a Heutagogical Approach - Salvatore Nizzolino; Agustí Canals (MDPI AG, 2024)
The Community of Inquiry (CoI) has increased in popularity in almost 25 years due to its adaptability which has spanned from asynchronous text-based environments up to a wide range of different settings. The CoI identifies the mutual interaction of three dimensions named presences. The survey to detect the perception of presences is a Likert-scale survey based on 34 items arranged in 10 subscales which are assigned as follows: 4 to teaching presence, 3 to social presence, and 3 to cognitive presence. Several studies identified alternative arrangements of the main components as a result of EFA and CFA. Consequently, the exploration of alternative settings keeps on revealing variations in the way presences interact with each other. The ongoing debate about whether to add a fourth dimension, specifically learning presence, has produced numerous publications but no definitive revised version of the survey. This study suggests an extension of the classical survey by incorporating a supplementary set of 12 items related to learning presence inspired by the theory of heutagogy (or self-determined learning). The sample for the experimental four-dimensional CoI framework comprised 55 university students. The analysis investigated the internal correlations of this extended survey, revealing positive expectations and opportunities for further adaptations.